Sustainability Implication of Residential Building Materials Considering Service Life Variability - Janjua, Shahana (Curtin University, 2021)
Each building is a complex product of components of variable materials and each building material is unique in its inherent properties including durability and thermal performance. This research has developed a life cycle sustainability assessment framework for buildings to address sustainability competently. Application of framework confirmed that service life of building, thermal performance of the building materials, use of by-products and recycled materials, and maintenance activities are crucial to sustainability performance of buildings.